No News Is News: Do Markets Underreact to Nothing? - Giglio, Stefano; Shue, Kelly (Review of Financial Studies, 2014)
As illustrated in the tale of “the dog that did not bark,” the absence of news and the passage of time often contain information. We test whether markets fully incorporate this information using the empirical context of mergers. During the year after merger announcement, the passage of time is informative about the probability that the merger will ultimately complete. We show that the variation in hazard rates of completion after announcement strongly predicts returns. This pattern is consistent with a behavioral model of underreaction to the passage of time and cannot be explained by changes in risk or frictions.